Intra-Arterial Therapy for Acute Ischemic Stroke - Abou-Chebl, Alex (S. Karger AG, 2013)
Intra-arterial therapy (IAT) for acute ischemic stroke treatment is evolving. Whereas the efficacy of recanalization with traditional intra-arterial fibrinolysis is relatively poor, mechanically based recanalization with multimodal approaches, stenting and mechanical embolectomy is more effective. Until recently, this has not resulted in overwhelming clinical benefit and has not always equated with reperfusion. The reasons for this are not clearly known but may include inadequate patient selection, poor technique, low operator experience, direct injury from thrombolytics or devices, microvascular occlusions, complications of general anesthesia, or some other unknown factors. Intracerebral hemorrhage still complicates 2-11% of procedures. Large prospective and randomized clinical trials are needed to determine the safety and efficacy of IAT be it pharmacological therapy, embolectomy, stenting, or multimodal therapy. Comparative studies between the newer stent retriever devices and intravenous tissue plasminogen activators may also be needed especially for the 3- to 4.5-hour window.